Optimum Design of Open Reinforced Concrete Circular Cylindrical Tanks Rest on Ground - Kadim, Jaffar A.; Jasim, Nabeel A. (Basrah Journal for Engineering Sciences, 2012)
A computer program has been generated to calculate the optimum dimensions and the amount of reinforcements for open reinforced concrete circular cylindrical tanks rest on ground. The design is based on limit state method for both ultimate and serviceability limit states in accordance with the British Standards B.S. 8110 and B.S. 5337. The cost of concrete, steel, and formwork are considered. The procedure is based on the interior penalty method to find the optimum solution for the non-linear programming problem. The tank consists of cylindrical wall and circular base and the joint between them was considered as partially fixed. The design variables consist of tank geometric variables in addition to steel content in seven positions. The effect of the design capacity of the tank, bearing capacity of the soil, unit price of steel and concrete, and finally unit cost of formwork was studied. It is found that the reduction of the bearing capacity of the soil linearly increases the cost of the tank. The increase of concrete and steel unit costs leads to increasing the tank height while the increase of formwork unit cost enhances the tank diameter, to reach the optimal design.